Role Of Endoscopic Gastric Biopsy in Patients With Chronic Dyspepsia For Diagnosis Of H. Pylori - Majeed, Muhammad Zafar; Mustafa, Ghulam; Ahsan, Haseeb (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: To determine the role of upper GI endoscopy and gastric biopsy to rule out H. Pylori (in patients with long-standing stomach symptoms), which is a manageable cause of chronic dyspepsia. Methods: This cross-sectional study was conducted at the medical OPDSheikh Zayed Hospital, Rahim Yar Khan. The sample size was 125 patients, having symptoms of chronic dyspepsia. Endoscopy of the participants has been done after getting informed consent. After histopathological analysis, the results were analyzed by SPSS version 23.0. The presence of H pylori has been evaluated in participants of different age groups, residences, symptoms, and conditions. Results: According to the analysed results, a total of 85 (68%) participants have been diagnosed with the presence of H. Pylori. Prevalence of H. Pylori is highest in the age group of 50 and above i.e. 28 (73.7%), followed by the age group 30-49 43 (67.2%), (p=0.5). There is a slightly higher ratio of H. Pylori in males i.e. 47 (72.3%) than in females i.e. 38 (63.3 Chronic dyspepsia patients who had a gastric ulcer on endoscopy had a dominant proportion of 20 (83.3%) who had H. pylori too on biopsy (p=0.07), similarly, patients who had duodenal ulcers also showed a dominant proportion 29 (80.5%) of a positive result for H. pylori on biopsy (p=0.05). Conclusion: The presence of H pylori was more than in patients above 30 years of age. So, it is better to have an endoscopic investigation to rule out any malignancy. Endoscopy is more beneficial and easily available in most parts of the country.